Impact of electronic bedside meal ordering systems on dietary intake, patient satisfaction, plate waste and costs: A systematic literature review. Issue 1 (19th January 2020) - MacKenzie‐Shalders, Kristen; Maunder, Kirsty; So, Daniel; Norris, Rebecca; McCray, Sally
Abstract: Aim: Hospital foodservices provide an important opportunity to deliver valuable dietary support to patients, address hospital‐acquired malnutrition risk and enhance patient satisfaction. Modifying the meal ordering process through the adoption of technology may actively engage patients in the process and provide an opportunity to influence patient and organisational outcomes. This systematic review was undertaken to evaluate the impact of electronic bedside meal ordering systems in hospitals on patient dietary intake, patient satisfaction, plate waste and costs. Methods: A systematic search following PRISMA guidelines was conducted across MEDLINE, CINAHL, EMBASE and Web of Science for randomised controlled trials and observational studies comparing the effect of electronic bedside meal ordering systems with traditional menus on dietary intake, patient satisfaction, plate waste and cost. The quality of included studies was assessed using the Quality Criteria Checklist for Primary Research tool. Results: Five studies involving 720 patients were included. Given the heterogeneity of the included studies, the results were narratively synthesised. Electronic bedside meal ordering systems positively impacted patient dietary intake, patient satisfaction, plate waste and costs compared with traditional menus. Conclusions: Despite the increase in healthcare foodservices adopting digital health solutions, there is limited research specifically measuring the impact of electronic bedside meal ordering systems on patient and organisational outcomes. This study highlights potential benefits of electronic bedside meal ordering systems for hospitals using traditional paper menu systems, while also identifying the need for continued research to generate evidence to understand the impact of this change and inform future successful innovations.